Bilateral Anterior Descending Artery Variant Mistaken as Chronic Occlusive Disease on Coronary Angiography: A Case Report - Bayu Aji, Kuncoro; Zhiwen, Tao (Jurnal KESANS : Kesehatan dan Sains, 2026)
The bilateral left anterior descending artery (LAD) variant is a rare congenital coronary anomaly defined by the presence of two LADs within the anterior interventricular groove. The shorter LAD terminates proximally, while the longer LAD extends distally to supply the apical region of the heart. This report describes a patient with typical stable angina pectoris in whom a bilateral LAD variant was identified. Coronary angiography revealed a proximal LAD occlusion, no ostial lesion was found in intravascular ultrasound examination. Subsequent coronary computed tomography angiography (CCTA) confirmed the presence of bilateral LADs. The shorter LAD originated from the left main coronary artery, and the longer LAD arose from the proximal conus branch of the right coronary artery, passing between the aorta and the right ventricular outflow tract. These imaging findings are consistent with a type VI bilateral LAD variant. Recognition of this rare anatomical configuration is crucial, as it may complicate the diagnosis and management of coronary artery disease. This case underscores the importance of multimodal imaging, particularly CT angiography, in accurately identifying coronary artery variations that can significantly influence clinical decision-making and interventional planning